The uses and abuses of weaponized interdependence - Drezner, Daniel W.; Farrell, Henry, 1970-; Newman, Abraham, 1973- (Brookings Institution Press, 2021)
"In exploring the conditions under which China, Russia, and the United States might be expected to weaponize control of information and manipulate the global economy, the contributors to this volume challenge scholars and practitioners to think differently about foreign economic policy, national security, and statecraft for the twenty-first century. The book addresses such questions as: What areas of the global economy are most vulnerable to unilateral control of information and financial networks? How sustainable is the use of weaponized interdependence? What are the possible responses from targeted actors? And how sustainable is the open global economy if weaponized interdependence becomes a default tool for managing international relations?"--